PEMBERIAN EDUKASI TENTANG PENTINGNYA IMUNISASI LENGKAP DAN VAKSINASI POLIO - Darma Karingga, Devangga; Nikmatul Nikmah, Anis (Stikes Yarsi Mataram, 2024)
Immunization is a public health intervention that is very effective in preventing serious infectious diseases. In this context, polio vaccination plays an important role because polio can cause permanent paralysis and even death. The aim of this activity is to increase knowledge, awareness and community participation about the importance of immunization, especially polio vaccination, through providing accurate information and eliminating misinformation, as well as facilitating access to health services. Method: This service begins with preparation and includes monitoring and evaluation. Where the interventions carried out are counseling, distribution of educational materials, door-to-door visits, and mobile posyandu to the community. Results: there has been a significant increase in knowledge, awareness and positive attitudes of the community towards immunization and polio vaccination. The evaluation showed a 45% increase in knowledge and a supportive change in attitudes. Conclusion: Service activities in Bandar Kidul Village succeeded in increasing the community's knowledge and positive attitudes towards polio immunization. This activity could be a model for other regions and is recommended to be held regularly with structured material and developed for maternal and child health (KIA).